Relict geomorphological and structural control on the coastal sediment partitioning, North of Bay of Biscay - Menier, D. (E. Schweizerbart'sche Verlagsbuchhandlung, 2016)
From the Glénan Island to Guérande plateau in south Brittany (France, Bay of Biscay), based on 10000 km of seismic lines, submerged rocky barriers/inherited structural elements were interpreted as the primary controls on variance of coastal topography and incision of palaeovalleys. Sediment infilling is regulated by valley morphology and fluctuation of energy conditions since the last marine transgression associated with the opening of the sea which in turn is a function of climate warming and sea level rising. Dynamics of sedimentation and their subsequent preservation are governed by the shape of the valley and exposure to coastal weather action. Given these structural, geomorphic and climatic constraints, the shoreward transport of sandy sediments is impeded. Thus, coastal topography and structural inheritance are critical factors determining volume of sediments transferred between seaward and landward regions. © 2015 Gebr. Borntraeger Verlagsbuchhandlung, Stuttgart, Germany.